The upper limit of thermoelectric figure of merit : importance of electronic thermoelectric efficiency - Li, Jing (2013)
To improve thermoelectric (TE) efficiency, the physical phenomenon of TE effect is revisited. The important TE figure of merit (FOM) is expressed in terms of powers, and it is mapped by two fundamental quantities. One is the electronic TE efficiency, which is purely determined by a probability distribution function of electron transport. Furthermore, electronic TE efficiency plays an important role in the upper limit of TE FOM, which is an important index to judge the quality of a TE device. For any TE device with FOM more than one, its electronic TE efficiency must be greater than 0.5. For demonstration purpose, the TE properties of silicon nanowire are investigated.